الأبعاد الجمالية في تصميم ملصقات بوسترات يوم الغدير - الطائي, جابر كاظم محمد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The research focuses on analyzing the artistic and design elements that reflect the cultural and religious values associated with this day. It addresses several main themes: Visual Dimensions: It addresses the use of colors, shapes, and lines, and how they influence the audience's emotions and impressions. It also discusses the importance of balance and harmony in design. Symbolism: It reviews the symbols used in posters, such as flags, logos, and writing, and how they reflect cultural and religious identity. Modern Technologies: It examines how modern technology, such as graphic design software, is used in poster design and its impact on the quality of the final work. Audience Interaction: It discusses how to attract the audience's attention and arouse their emotions through good design, and the role of posters in promoting religious awareness and community celebrations. Case Study: The research includes an analysis of a selection of posters used in celebrations, providing aesthetic and detailed evaluations of each poster. The research concludes that good aesthetic design for Ghadeer Day posters plays a vital role in promoting understanding and celebration of culture and religion, and enhances community connection to its heritage. The study also recommends developing designers' skills in this field to leverage aesthetic dimensions in expressing values and beliefs.